Strategi Pemberdayaan Kehidupan Sosial, Agama dan Ekonomi pada Keluarga Single Mother di Kelurahan Rojoimo Kabupaten Wonosobo - Mustika Septi Handini (Tabsyir: Jurnal Dakwah dan Sosial Humaniora, 2024)
Single mothers in the Wonosobo area always increase every year, divorce is the main reason. The strategy of empowering social, religious and economic life in single mother families is very important for the life of single mothers in the midst of incomplete social and family life. The role of Islamic religious counselors is very much needed to realize the empowerment of social, religious and economic life in single mother families where they live among the majority of intact families. This research aims to find strategies for empowering social, religious and economic life in single mother families, especially in the Rojoimo sub-district. Wonosobo Regency. To achieve this goal, this research applies a qualitative approach to single mother families in the Rojoimo sub-district of Wonosobo. The findings of this research identify that Islamic religious instructors have a role in empowering single mothers. The empowerment strategy is carried out by applying social roles, economic roles and religious roles.